What determines the dismount side on parallel bars? - Rodriguez-Redondo, Y.; Martin-Blazquez, J.; Leon, K. (Science of Gymnastics Journal, 2025)
The objectives of this study are (1) to determine what aspects should be taken into account when a gymnast chooses his dismount side on parallel bars and (2) to check if there is a direct relationship between the direction of rotation in the twists and the dismount side on parallel bars. The performance of 45 gymnasts at the World Artistic Gymnastics Championships between 2020 and 2023 were analysed using video footage. Data were recorded in Microsoft Excel, and duplicate gymnasts were excluded to avoid repeating data. Chi-square tests were performed and Cramer's V was calculated with the Jamovi program. Additionally, artistic gymnastics coaches were interviewed to discuss the results. The results of the chi-square test show a significant relationship between the direction of rotation on the floor and the dismount side on parallel bars(x² = 27.4, p < 0.01). The Cramer's V value (0.453) indicates a moderate relationship. Furthermore, it was found that performing a twist in the levorotatory direction is associated with dismounting on the left side of the parallel bars (the most common pattern), and vice versa. The dismount side may be influenced by factors such as coordination, strength, or the gymnast's personal preference. Some coaches noted that the support arm in elements such as the Healy, Stutz or Diamidov can be a determining factor when choosing the dismount side on parallel bars.